PEMANFAATAN USB FLASHDISK SEBAGAI KUNCI PADA KEAMANAN DATA DENGAN PENERAPAN ALGORITMA ELGAMAL - Putri Rahayu, Rizka; Fauzi, Achmad (STMIK KAPUTAMA, 2020)
Cryptography is one of the sciences that studies mathematical techniques related to aspects of information security such as confidentiality. One cryptographic algorithm is the Elgamal algorithm to encrypt and decrypt messages that use a USB flash drive as a key. Flashdisk is widely used by students for data storage, therefore choosing flash as an encryption key is also very important and wants to be a reason to use flash as an encryption key and supporting device for data security. The use of flash as a medium for more secure data security. The problem that will be solved by using this system is security in the form of text files. in the process of encrypting text messages that can be read (plaintext) will be encrypted with an elgamal algorithm by using an elgamal algorithm key to produce a ciphertext. Implementation of the system uses visual basic.net software 2010. Then the decryption process is the process of returning a secret message (ciphertext) to the original message (plaintext). The USB device used to encrypt the plaintext must be the same as the USB device used to describe the ciphertext if the USB devices used are not the same, the decryption results are not the same as before encryption.